GRAND DESIGN OF EDUCATIONAL INSTITUTIONS IN CHARACTER EDUCATION (An analysis of problems and New Formulations, in the approach to character education) - Reksiana, Reksiana (IAIN Ambon, 2019)
the existence of differences of view to education children character, and can be classified in several categories and theories. This difference is seen as some figures say families or tualah people are the most important in providing character education. Others argue sekolahlah that is most vital in respect of containers of character education. This article uses a qualitative approach, with the kind of Library Research. Therefore, the overall data focuses on books or papers relating to discussion of